Quality of parenting programs and child development outcomes: The case of Peru's Cuna Mas - M. Caridad Araujov; Marta Dormal; Marta Rubio-Codina (Inter-American Development Bank (IDB), 2018)
This paper analyzes the association between quality of parenting programs and child development outcomes. It focuses on parenting programs delivered through home visits (i.e., home visiting programs) in which a paraprofessional works with the caregiver to improve parental practices, skills and knowledge of child development, with an application to the Peruvian national program Programa Nacional Cuna Mas. Home visiting quality is measured through the Home Visit Rating Scale, version A+2 (HOVRS-A+2), and child development outcomes through the Ages and Stages Questionnaires (ASQ-3) and the Bayley Scales of Infant and Toddler Development (Bayley-III). The empirical analysis used is descriptive in nature. Results show that home visiting quality scores are significantly associated with our measures of child development, but this association is not consistent across all measures.
Keywords: I12; J24; O15; 330; home visiting; quality; child development; HOVRS-A+2; ASQ-3; Bayley-III